Sanitation Overview On The Working Area - Kadarusman, Haris; Sutopo, Agus; Hasan, Amrul; Prianto, Nawan (MIDWIFERY JOURNAL, 2025)
Background: Communicable diseases remain a health problem in all regions of Indonesia, especially environmentally-based diseases such as Acute Respiratory Infections and Diarrhea, which are consistently among the top ten diseases in every region of Indonesia, including on the working area of Hajimena Health Center area in Natar District, South Lampung Regency.Objectives: To reveal the sanitation conditions on the Hajimena Health Center’s service area, comprised of clean water facilities, household toilets, waste management, and handwashing with soap behavior.Methods: The study was conducted by surveying 365 households, and the sample distribution was consisted of 200 households at Hajimena Village, 105 households at Pemanggilan Village, and 60 households at Sidosari Village. Data collection was carried out through home observations and interviews with the respondents i.e. head of the family or housewife of the selected sample. Data analysis was performed using statistical univariate analysis by calculating the frequency distribution and percentage for each variable.Results: The provision of drinking water, family latrine, and waste management is in good condition in more than 85% of the households, while good household wastewater disposal is still below 80%. For handwashing aspect, more than 95% of the respondents wash their hands before or after activities, but not all use soap. Those who wash their hands with soap range from 79% to 89%, and there are still 1.1% - 2.65% of respondents who rarely or do not wash their hands before or after activities. Regarding with food preparation, about 79.18% of respondents wash their hands with soap beforehand, 18.9% wash their hands but without using soap, and 1.79% rarely wash their hands.Conclusion: The sanitation conditions and handwashing with soap behavior on the working area of Hajimena Health Center area are quite good Key Words : Sanitation, Overview, Hands Wash  Latar belakang : Penyakit menular masih menjadi masalah kesehatan disemua wilayah di Indonesia, khususnya penyakit menular berbasis lingkungan seperti Infeksi Saluran Pernafasan Akut, Diare dan penyakit lainnya yang selalu ada dalam 10 (sepuluh) besar penyakit disetiap wilayah di Indinonesia termasuk di Wilayah Puskesmas Hajimena Kecamatan Natar Kabupaten Lampung Selatan.Tujuan: Diketahuinya gambaran Sanitasi di Wilayah Puskesmas Hajimena yang meliputi Sarana Air Bersih,  Jamban Keluarga, Pengelolaan Sampah dan Perilaku Cuci Tangan Pakai SabunMetode : Penelitian dilaksanakan dengan melakukan survey terhadap 365 Rumah Tangga di wilayah kerja Puskesmas Hajimena dengan distribusi sampel sebanyak 200 Rumah di Desa Hajimena, 105 Rumah di Desa Pemanggilan dan 60 Rumah di Desa Sidosari. Pengumpulan data dilaksanakan dengan melakukan observasi rumah dan wawancara dengan kepala keluarga dan ibu rumah tangga sampel terpilih. Analisa data menggunakan Uni Variat dengan Distribusi Frekwensi pada masing-masing variableHasil : Untuk penyediaan air Minum, jamban Keluarga, dan pengelolaan sampah sudah lebih dari 85 % baik, hanya pembuangan air limbah rumah tangga masih dibawah 80 %. Untk cuci tangan sudah lebih dari  95 % ibu atau kepala keluarga melakukan cuci tangan sebelum atau sesudah melakukan kegiatan, namun belum semuanya mencuci tangan pakai sabun. Ibu.  Mereka yang mencuci tangan pakai sabun berkisar antara 79 % sampai 89 % dan masih ada 1,1 % - 2,65 % ibu atau kepala keluarga yang jarang atau tidak mencuci tangan setelah atau sebelum melakukan kegiatan.Kesimpulan : Untuk kondisi sanitasi dan perilaku cuci tangan pakai sabun di wilayah Puskesmas Hajimena sudah cukup baik.Pakai Sabun masih 79,18 % ibu yang mencuci tangan pakai sabun sebelum menyiapkan makanan, 18,9 % mencuci tangan tetapi tidak menggunakan sabun dan masih ada 1,79 % jarang mencuci tangan sebelum menyiapkan makanan